2012
DOI: 10.1177/001440291207900102
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Alternative Route Special Education Teacher Preparation

Abstract: In this study, the authors estimated costs of alternative route preparation to provide states a basis for allocating training funds to maximize production. Thirty-one special education alternative route program directors were interviewed and completed cost tables. Two hundred and twenty-four program graduates were also surveyed. The authors describe program characteristics, including costs; program content; and participant demographics, including employment history and future plans. Four program types are iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Many of them have also worked as special educators without a formal qualification as class teachers or as preschool teachers. This means that they are well-educated and experienced students and a little older than traditional student teachers, which is the case in many countries (also see Sindelar et al 2012). This also means that they have inside information about special education in schools before they begin their studies.…”
Section: Remarks About the Amount And Role Of Special Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them have also worked as special educators without a formal qualification as class teachers or as preschool teachers. This means that they are well-educated and experienced students and a little older than traditional student teachers, which is the case in many countries (also see Sindelar et al 2012). This also means that they have inside information about special education in schools before they begin their studies.…”
Section: Remarks About the Amount And Role Of Special Educationmentioning
confidence: 99%
“…In an examination of the content of special education studies, it is interesting to observe that around the world similar kinds of issues are included in the studies. They include foundations of general and special education as well as special and general education methods (see Romero-Contreras et al 2013;Sindelar et al 2012). According to Farrell (2009), the underlying aspects that contribute to the understanding of special education are medical, social, psychotherapeutic and pedagogical.…”
Section: The Content Of Special Educator Studiesmentioning
confidence: 99%
“…In contrast, alternative-route graduates have been judged to be at least minimally competent overall; in one study (Sindelar et al, 2004), some were rated significantly higher on other Praxis III criteria (e.g., teacher professionalism) than were graduates of traditional programs. Furthermore, some alternative-route programs have been successful in attracting highly diverse trainee cohorts (Rosenberg, Boyer, Sindelar, & Misra, 2007;Sindelar et al, 2009). Typically, these are internship programs in which practicing teachers undertake preparation as a condition of employment.…”
Section: Our Research Foundationmentioning
confidence: 99%
“…Typically, these are internship programs in which practicing teachers undertake preparation as a condition of employment. Internship programs represent one of four approaches to alternative-route programming identified by Sindelar et al (2009), who also estimated the costs associated with different models. They found that fast-track programs were less expensive in the short term but that they produced teachers who were less committed to the field.…”
Section: Our Research Foundationmentioning
confidence: 99%
“…Some were older than the typical urban residency participant, but all participants, near retirement or just finishing college, were eager to remain in their field and teach. Many were considering becoming special education teachers in math or other fields, yet others first realized that people with special needs might be in their college classes (Sindelar, Dewey, Rosenberg, Corbett, Denslow, 2012).…”
Section: What the Literature Says About Non-traditional Teacher Prep mentioning
confidence: 99%